Maximizing Research on Long COVID using FHIR and OMOP - Eugenia RINALDI; Lorenzo CANZIANI; Salvatore CAUTADELLA; Chiara DELLACASA; Anna GORSKA; Juan Mata NARANJO; Thomas OSMO; Miroslav PUSKARIC; Elisa ROSSI; Sylvia THUN (Applied Medical Informatics)
In 2020 The European commission funded the ORCHESTRA project with the aim to join the efforts of several European research centers in the research around the COVID-19 disease. One of the main challenges was to harmonize data across the different cohorts and countries. The introduction of standard terminologies such as SNOMED CT or LOINC helped establish a common language within the project. Over 3500 variables from several information categories were mapped to international codes from standard terminologies. After four years since the start of the pandemic, the study of long COVID seems to be of particular relevance due to the long-term effects that some people keep experiencing even after the infection has disappeared. To facilitate this research, we selected the ORCHESTRA variables that concerned long COVID and mapped them to the standards FHIR and OMOP to possibly support further data exchange with other research organizations.